An exploration of nursing informatics competency and satisfaction related to network education. - Lin J; Lin K; Jiang W; Lee T (Journal of Nursing Research (Taiwan Nurses Association), 2007)
The rapid development of computer technology has driven the growth of the Internet, which has made access to daily services more timely and convenient. Network education strategies for long-distance nursing education are increasingly being implemented to overcome distance barriers and allow nurses to obtain more knowledge. The purpose of this study was to investigate the relationship between the informatics competency of nurses and their satisfaction regarding network education as well as to explore related factors. A total of 218 nurses answered an online questionnaire after completing 4 hours of network education at their appropriate clinical level. Descriptive and inferential statistics were applied to analyze data. Study results found that nurses who took computer training less than 3 hours per week, were unable to connect to a network, or held an associate degree as their highest level of education achieved a lower nursing informatics competency than those who were older, were certified at an N4 clinical level, had previous online training experience or attended 4 or more course hours each week. Those who participated in the network education course more than 4 hours per week and owned their own computers were more satisfied with network education. Nurses who had higher nursing informatics competency were also more satisfied with network education. Network education not only enhances learners' computer competency but also improves learning satisfaction. By promoting network education and improving nurses' hardware/software skills and knowledge, nurses can use networks to access learning resources. Healthcare institutions should also enhance their computer infrastructures, and increase the interest of nurses to learn and apply network skills in clinical practice.